A study on the market potential of Petronas NGV in Sabah / Roziah Suhailen - Suhailen, Roziah (2007)
The purpose of this study is to determine the market potential of PETRONAS NGV in Sabah. The study was conducted among 120 respondents and selected randomly in Kota Kinabalu area. This study involved respondents from government employee, private employee, student and public transportation. A descriptive research approach has been chosen in this study. This research approach was used as it would explain an accurate description of the variables in the research questions that would be extremely supported by later findings and analysis. The study revealed that, most of the respondents agree that PETRONAS NGV could be accepted in Sabah market. There are some recommendations given by the respondents and PETRONAS can consider these recommendations in order to promote the PETRONAS NGV in Sabah market.